Synthesis and structural studies on (1-x) Bi(Mg1/2Ti 1/2)O3-xPbTiO3 piezoceramics - Upadhyay A.; Pandey R.; Anand S.; Singh A.K. (My University, 2025)
We present here the structural studies on (1-x)Bi(Mg1/2Ti1/2)O3-xPbTiO3 (BMT-xPT) piezoceramics with x=0.28, 0.37 and 0.45 using powder x-ray diffraction data. Rietveld refinement of powder x-ray diffraction data reveals the tetragonal structure (space group P4mm) for the compositions with x>0.40 and rhombohedral (space group R3m) for the compositions with x<0.30 of BMT-xPT ceramics. The morphotropic phase boundary is found for the intermediate composition with 0.30<x<0.40, where the coexistence of two phases are observed. © 2014 AIP Publishing LLC.